Pengaruh Kompetensi Sumber Daya Manusia dan Pemanfaatan Teknologi Informasi terhadap Penerapan Akuntansi Berbasis Akrual pada Badan Pengelolaan Keuangan dan Aset Daerah di Kabupaten Kutai Kartanegara - Nur Laila Achmad; Dwi Risma Deviyanti; Abdul Gafur (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2020)
This study aims to determine the effect of competence in human resources and the use of information technology has an effect on the application of accrual-based accounting. The sample of this study was all employees in the Badan Pengelolaan Keuangan dan Aset Derah (BPKAD) of Kutai Kartanegara with a population of 93 people. Data collection is done by questionnaire survey. The data of this study are primary data. This research uses quantitative methods. Analysis tools using Smart PLS 3.0. The results of this study indicate that the competence of human resources has a positive and significant effect on the application of accrual-based accounting and the use of information technology has a positive and significant effect on the application of accrual-based accounting.